2018
DOI: 10.3390/toxins10100402
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Contamination of Water with Saxitoxin Near the Dam of the Irkutsk Hydropower Station Reservoir (East Siberia, Russia)

Abstract: An area of discolored water 50 m wide and 30 m long was found in September 2017 close to the dam of the Irkutsk hydroelectric power station. Water from this spot was sampled for investigation in the present study. Microscopic analysis revealed that the suspended matter in the sample was composed of clumps of filaments, vegetative cells, akinetes and heterocysts that formed short filaments and solitary cells. This matter was found to consist of partially degraded cells of the cyanobacterium Dolichospermum lemme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
9
0
4
Order By: Relevance
“…Аликвоты супернатанта (160 мкл) переносили в стеклянные виалы и удаляли растворитель на вакуумной центрифуге при 60°С. Получение производных с 2,4-динитрофенил-гидразином и определение методом ЖХ -МС выполняли в соответствии с (Grachev at al., 2018).…”
Section: отбор пробunclassified
See 3 more Smart Citations
“…Аликвоты супернатанта (160 мкл) переносили в стеклянные виалы и удаляли растворитель на вакуумной центрифуге при 60°С. Получение производных с 2,4-динитрофенил-гидразином и определение методом ЖХ -МС выполняли в соответствии с (Grachev at al., 2018).…”
Section: отбор пробunclassified
“…Таблица (Grachev at al., 2018) 3 (Belykh et al, 2015а) 4 (Belykh et al, 2015б) Продуцентом сакситоксина, обнаруженного в чрезвычайно высокой концентрации в воде из приплотинного участка акватории водохранилища Иркутской ГЭС, оказался вид Dolichospermum lemmermannii (Grachev at al., 2018). В геноме этого вида был обнаружен ген sxtA, участвующий в синтезе сакситоксина, а в биомассе -токсин в довольно высокой концентрации.…”
Section: Issn 2412-1908; Http://journalasuru/biolunclassified
See 2 more Smart Citations
“…The amount of STXs found in reservoirs around the world varies considerably depending on the period of the year and the density of the cyanobacteria. In Brazilian reservoirs, concentrations from 3.0 ng L −1 to 13.18 µg STX equivalents (STX equiv ) L −1 have been recorded (Fonseca et al 2015;Calado et al 2017;Casali et al 2017;Silva et al 2020), whereas concentrations as high as 193 and 2900 ± 900 μg L −1 have been reported in the United States (Trainer and Hardy 2015) and Russia (Grachev et al 2018), respectively. These neurotoxins prevent the propagation of nerve impulses by binding to and blocking sodium channels in the axons of neurons, which leads to muscle paralysis and the consequent death of vertebrates from respiratory arrest (Wiegand and Pflugmacher 2005).…”
Section: Introductionmentioning
confidence: 99%